Azure Data Factory Cookbook : Build and manage ETL and ELT pipelines with Microsoft Azure's serverless data integration service /: Build and manage ETL and ELT pipelines with Microsoft Azure's serverless data integration service. (2020) - Anoshin, Dmitry; Foshin, Dmitry; Storchak, Roman; Ireton, Xenia
No abstract available